The Legal Position of Cancellation of Deed of Grant Due to Intervention Lawsuit - Basmi, Hasriadi (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
This study aims to find out and analyze the form of third party intervention in a lawsuit for canceling a grant deed, to find out and analyze the legal standing of the cancellation of a grant deed due to an intervention lawsuit, and to find out and analyze solutions to avoid the emergence of an intervention lawsuit to cancel a grant deed. This research is empirical legal research, and was conducted in Bombana District, Southeast Sulawesi Province. Methods of data collection using interview techniques and field observations. All data, both Primary Data and Secondary Data, were analyzed using qualitative analysis techniques. The results of this study indicate that: (1) The form of third party intervention in a grant deed cancellation lawsuit can be in the form of:Voegings, namely the participation of a third party on its own initiative in examining civil disputes to defend one of the parties, either the plaintiff or the defendant, Tussenkomst, namely the participation of a third party on its own initiative in the examination of civil disputes, but does not side with either party, either the plaintiff or the defendant, but for the sake of defending his own interests, and Vrijwaring or guarantee, namely the participation of a third party in the examination of civil disputes because one of the parties is withdrawn to bear it. (2) The legal status of the cancellation of the deed of grant due to an intervention claim, in simple terms, is related to factors 1) Concerning the Sitting Case; 2) Intervention Lawsuit. In principle, being an intervention plaintiff is a right, so it can be done or not done. But in the case when carrying out a lawsuit, there are parties who should be used as Intervening Defendants but the plaintiffs do not do so in their lawsuit, an Error in Persona will occur. namely Lawsuit of less parties (Plurium Litis Consortium). (3) The solution to Avoid Intervention Lawsuits to Cancel Grant Deeds is to intensify legal counseling by Notaries/PPATs regarding various laws and regulations related to Notary/PPAT products including grants. In addition, the precautionary principle of the Notary/PPAT also needs to be further improved, in order to avoid formal and material defects.Keywords: Grants; Interventions; Legal.